Interactions and performance analysis of epoxidized palm oil/unsaturated polyester resin: Mechanical, thermal, and thermo-mechanical properties - Mustapha, Siti Noor Hidayah; Rahmat, Abdul Razak; Mustapha, Rohani (SAGE Publications Ltd, 2022)
In this work, an alternative of bio-thermoset resin for composite applications was synthesized using unsaturated polyester resin (UPE) and epoxidized palm oil (EPO). The main purpose of this study is to reduce the dependency on petroleum and improve the toughness properties of UPE by partially introduced renewable source triglyceride, EPO in the UPE chain. The UPE resin blends with 10, 20, and 30 wt% EPO oil were synthesized by using benzoyl peroxide as an initiator. The samples were cured in an oven at 100°C and 160°C for 4 h. The interaction of the blend was studied by the FTIR test supported by the SEM test. The effects of EPO loadings in UPE on the mechanical, thermal, and thermo-mechanical properties were also being studied. The addition of EPO physically interacted in the system and acted as a lubricant. The higher the addition of EPO in UPE has increased the elongation at break and impact strength of the UPE resin, which indicated an increase in mobility and toughness of the UPE chain. The developed UPE/EPO blends resin also exhibited higher thermal stability than the neat UPE, thereby showing potential to be used in a wide range of composite applications.